Enhanced biogas production in anaerobic digestion of sludge medicated by biochar prepared from excess sludge: Role of persistent free radicals and electron mediators. (March 2022) - Liu, Xiang; Meng, Qingting; Wu, Fengjie; Zhang, Chen; Tan, Xuejun; Wan, Chunli
Highlights: The PFRs in biochar prepared from sludge had bactericidal effects on microorganisms. Biochar possessed the electron transfer ability similar to an electron mediator. The addition of biochar boosted the production of biogas by a maximum of 54.5%. The enhancing effect of biochar prepared at 400℃ was better than at 600℃. Abstract: The addition of biochars to promote the efficiency of anaerobic digestion (AD) has widely received concerns. However, the role of persistent free radicals (PFRs) and the electron transfer ability of biochar in AD has not yet been noticed. In this study, biochars were prepared from excess sludge under 400 °C (B400) or 600 °C (B600) and different ratios of sludge to biochar (5:1, 10:1, 20:1) were applied in the AD of sludge. The results verified that PFRs in biochar participated in the sterilization of microorganisms in sludge, resulting in the release of organic matters. Similar to electron mediators, biochars possessed electron exchangeability and the addition of biochars boosted the biogas production by maximum of 54.5%. The enhancing effect of B400 surpassed that of B600 as high temperature destroyed functional groups and reduced the defect degree of biochar. This study achieved in-situ resource utilization and provided references for the improvement of anaerobic digestion.